2001
DOI: 10.1034/j.1600-0528.2001.029001073.x
|View full text |Cite
|
Sign up to set email alerts
|

Dentists' perceived stress and its relation to perceptions about anxious patients

Abstract: Dentists' perceptions about the stressfulness of dental practice, their perceptions about dental anxiety and its management were surveyed in a descriptive study. A mailed questionnaire was completed by 216 randomly selected Danish private dentists. Of these, nearly 60% perceived dentistry as more stressful than other professions. Dentist perceptions of the most intense stressors were (ranked): 1) running behind schedule, 2) causing pain, 3) heavy work load, 4) late patients and 5) anxious patients. Bivariate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
1
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 0 publications
6
84
1
6
Order By: Relevance
“…12 Research conducted by the Centre for Special Dental Care found that specially trained practitioners were more effective in dealing with dentally anxious patients than general practi tioners. 13 This suggests that appropriate training for dentists in managing den tally anxious patients is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…12 Research conducted by the Centre for Special Dental Care found that specially trained practitioners were more effective in dealing with dentally anxious patients than general practi tioners. 13 This suggests that appropriate training for dentists in managing den tally anxious patients is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, studies have suggested that dentistry generates more stress than any other profession, primarily because of the nature and working conditions of the dental surgery. [5][6][7] Statistics on dentistry and cardiovascular disease, alcoholism, drug abuse, divorce and elevated rates of suicide suggest that the typical life of a general dental practitioner (GDP) is a stressful one. [8][9][10] However, there has been a lack of recent comprehensive surveys investigating stress, health and the GDP.…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, research has demonstrated that dentistry may be a stressful occupation, with studies from as far afi eld as Denmark, 22 the United States, 23 Israel, 24 the United Kingdom [2][3][4]8,9 and Southern Thailand 25 confi rming this. A lack of career perspective has been found to be a stress factor most related to burnout in a survey of Dutch dentists.…”
Section: Discussionmentioning
confidence: 99%